Analisis Kompetensi Pedagogik Guru dalam Pembelajaran Bahasa Indonesia di SMA PGRI Larantuka - Yustina Tuto Tukan; Vincensius Crispinus Lemba; Sirilus Karolus Keroponama Keban (Social Science Academic, 2023)
There are several indicators of each aspect as a pedagogic competency that must be addressed by Indonesian language subject teachers at SMA PGRI Larantuka, in particular, namely indicators (1) checking regularly by asking students about material understanding, (2) ability connecting new things with students' prior knowledge, (3) supervising all students by going around responding to students' responses to the material being taught, (4) ensuring the level of students' understanding of learning material, (6) adjusting students' abilities to concentrate on receiving lessons according to the level of development, giving students lots of opportunities to ask questions, (7) using teaching aids or audiovisuals, (8) correctly identifying students' talents, interests, potential and learning difficulties, and (9) using questions to find out understanding learners.